Pengaruh Adosa Dan Karuna Terhadap Karakter Tanggung Jawab Mahasiswa STAB Maha Prajna - Nyaman; Diono, Wahyu (Sekolah Tinggi Agama Buddha Maha Prajna Jakarta, 2026)
The decline of academic integrity in the digital era, reflected in practices such as plagiarism, assignment outsourcing, and weak discipline, highlights the urgent need to strengthen students' sense of responsibility. This study aims to examine the effects of adosa and karuna on the responsibility character of students at STAB Maha Prajna Jakarta. The novelty of this study lies in its empirical investigation of two Buddhist ethical values, adosa and karuna, as predictors of responsibility character within the context of Buddhist higher education, an area that remains underexplored in quantitative research. The study employed a quantitative approach using a survey design involving 60 students. Data were collected through a Likert-scale questionnaire and analyzed using multiple linear regression. The results indicate that adosa and karuna jointly have a significant effect on students' responsibility character (F = 3865.428; p < 0.001), with the model accounting for 99.3% of the variance (R² = 0.993). Partially, both variables were found to have positive and significant effects, with karuna making a more dominant contribution than adosa. These findings suggest that the development of students' responsibility should not rely solely on external discipline, but also on the internalization of self-restraint and compassion as ethical foundations of academic behavior. Keywords: adosa, karuna, responsibility character, students, Buddhist higher education.